Philips 3200 LatteGo / Siti Sarah Daud - Daud, Siti Sarah (2022)
This assignment is about identifying the problem with the product. The company that I have chosen is Philips. From their variety of products, I have chosen the Philips 3200 LatteGo to do my analysis. In this case study, I have done the SWOT analysis to identify the strength, weaknesses, opportunities, and threats of the Philips 3200 LatteGo. The main problem I identified on this Philips 3200 LatteGo is that the machine produces low quality taste of coffee, unlike the other coffee machines, I can come up with the best solution which is using the same system as it already has and upgrade the machine by doing a joint-venture with Nespresso.